Studi Kelayakan Alur Sungai dan Kanal di Kota Makassar Sebagai Media Transportasi Air - Elti Eka Prasetia; Kamran Aksa; Ilham Yahya (Fakultas Teknik Universitas Bosowa, 2023)
Abstract. This study aims to determine the feasibility of the width and depth of river and canal shipping lanes in Makassar City as well as directions that can be taken to support its development. This study used quantitative and qualitative approach methods with data collection processes carried out through observation, documentation, interviews in the research area and literature studies. Furthermore, it is analyzed using a feasibility analysis of shipping lanes by calculating the width and depth of the river that is feasible to be used as a medium of transportation with speedboats as a benchmark for transportation facilities that have been used by people in the research environment. Based on the results of the analysis carried out, it was found that the width of the feasibility that can be carried out by transportation activities using speedbots is 14 meters for one direction and 28 for two directions. For kedamannya that is 0.66 m. To maximize the function of canals and rivers as transportation media, it is necessary to carry out activities to neutralize the environmental areas of rivers and canals both from garbage and illegal developments carried out by the community Abstrak. Penelitian ini bertujuan untuk mengetahui kelayakan lebar dan kedalaman alur pelayaran sungai dan kanal di Kota Makassar serta arahan yang dapat di lakukan dalam mendukung pengembangannya. Penelitian ini menggunakan metode pendekatan kuantitatif dan kualitatif dengan proses pengambilan data yang di lakukan melalui kegiatan observasi, dokumentasi, wawancara pada daerah penelitian serta studi literatur. Selanjudnya, di analisis menggunakan Analisa kelayakan alur pelayaran dengan menghitung lebar dan kedalaman sungai yang layak untuk di gunakan sebagai media transportasi dengan kapal speedbot sebagai tolak ukur sarana transportas yang telah di gunakan oleh masarakat di lingkungan penelitian. Berdasarkan hasil Analisa yang di lakukan dapatkan bahwa lebar kelayakan yang dapat di lakukan aktifitas transportasi dengan menggunakan speedbot ialah 14 meter untuk satu arah dan 28 untuk dua arah. Untuk kedamannya yaitu 0,66 m. untuk memaksimalkan fugsi kanal dan sungai sebagai media transportasi, perlu di lakukan kegiatan menetralisir area lingkungan sungai dan kanal baik dari sampah maupun pembangunan-pembangunan illegal yang di lakukan oleh masyarakat.